Evaluasi Unjuk Kerja Kompresor Screw SH250 di PT Pertamina EP Asset 4 CPP Gundih - Anugrah Zainuri; Kasturi Kasturi (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to analyze the performance of the SH250 Screw compressor based on field observation data. Based on the observation and data analysis, several conclusions can be drawn. First, the actual capacity of the compressor decreased by about 14.7485% from the design condition. This decrease is caused by the difference in operational pressure which is lower than the design pressure. Secondly, the power generated by the current compressor is about 136.143kW, which is lower than the design power of 250 kW. This decrease in power is due to the low input temperature. These findings indicate the importance of considering actual operational conditions in optimizing compressor performance. In this context, further adjustments or evaluations are recommended to ensure optimal performance of the SH250 Screw compressor. Factors such as operational pressure and input temperature should be carefully considered to achieve the expected results. This research provides valuable insights for the industry in understanding the factors affecting compressor performance and provides a basis for future performance improvements. These efforts are expected to improve operational efficiency and reduce potential losses in the use of the SH250 Screw compressor.